Pleasure-Suffering at work: A case study with rural school teachers - Ribeiro Marinho, Paulo Roberto [UNESP]; Gava Schmidt, Maria Luiza [UNESP]; Vasconcelos, Mario Sergio [UNESP] (Univ Federal Santa Maria, 2021)
This study provides an analysis of the rural schools teachers' perception about the pair pleasure-suffering in their work context. It supported by the theory of Psychodynamics of Work. The literature search included the studies on teacher disconfort in addition to the theoretical contributions of psychodynamics that contribute to understand the experiences of pleasure and suffering at work. The study examined the mentioned teachers' work context according to the following dimensions: Work Organization (OT), Working Conditions (CT), Socioprofessional Relations (RSP) and the pair Pleasure-Suffering at Work (PST). This is a qualitative study with an outlined case study in which we applied sem istructured and open interviews which were submitted to an analysis of the context. The research was conducted with 20 teachers from two rural schools in the interior of Sao Paulo (SP). The results indicated that teachers have experienced pleasure and suffering at work, but the last one is the predominant sense. The teachers' experiences of pleasure are associated with their own educational activity as well as with their relationship with students, families and other teachers. On the other hand, the experiences of suffering at work are related to an exorbitant workday, the lack of support, difficulty in accessing schools and conflicting relationships. This study intends to contribute to the understanding of the experiences of pleasure and suffering at work and their reflexes in the health of teachers and school institutions.
Keywords: Teacher; Rural school; Pleasure-suffering; Worker's health